Hypertrophic osteoarthropathy in adults with cystic fibrosis. Issue 5 (October 1976) - Matthay, M A; Matthay, R A; Mills, D M; Lakshminarayan, S; Cotton, E
Abstract : Three adult patients with cystic fibrosis presented with arthralgia, and investigation for the usual causes of arthritis proved negative. Radiographs of long bones revealed periostitis and new bone fromation characteristic of hypertrophic osteoarthropathy. Symptomatic improvement occurred after analgesic and anti-inflammatory therapy. In patients with cystic fibrosis and bone or joint pain, the diagnosis of hypertrophic osteoarthropathy should be considered and long bone radiographs obtained.